The effects of entry in bilateral oligopoly - Alex Dickson (Games, 2013)
The purpose of this paper is to study the effects of entry into the market for a single commodity in which both sellers and buyers are permitted to interact strategically. With the inclusion of an additional seller, the market is quasi-competitive: the price falls and volume of trade increases, as expected. However, contrary to the conventional wisdom, existing sellers' payoffs may increase. The conditions under which entry by new sellers raises the equilibrium payoffs of existing sellers are derived. These depend in an intuitive way on the elasticity of a strategic analog of demand and the market share of existing sellers, and encompass entirely standard economic environments. Similar results are derived relating to the entry of additional buyers and the effects of entry on both sides of the market are investigated.
Keywords: 330; bilateral oligopoly; entry; comparative statics; aggregative games